Metabolic disruption in context: Clinical avenues for synergistic perturbations in energy homeostasis by endocrine disrupting chemicals - Sargis, Robert M (Endocr Disruptors (Austin), 2015)
The global epidemic of metabolic disease is a clear and present danger to both individual and societal health. Understanding the myriad factors contributing to obesity and diabetes is essential for curbing their decades-long expansion. Emerging data implicate environmental endocrine disrupting chemicals (EDCs) in the pathogenesis of metabolic diseases such as obesity and diabetes. The phenylsulfamide fungicide and anti-fouling agent tolylfluanid (TF) was recently added to the list of EDCs promoting metabolic dysfunction. Dietary exposure to this novel metabolic disruptor promoted weight gain, increased adiposity, and glucose intolerance as well as systemic and cellular insulin resistance. Interestingly, the increase in body weight and adipose mass was not a consequence of increased food consumption; rather, it may have resulted from disruptions in diurnal patterns of energy intake, raising the possibility that EDCs may promote metabolic dysfunction through alterations in circadian rhythms. While these studies provide further evidence that EDCs may promote the development of obesity and diabetes, many questions remain regarding the clinical factors that modulate patient-specific consequences of EDC exposure, including the impact of genetics, diet, lifestyle, underlying disease, pharmacological treatments, and clinical states of fat redistribution. Currently, little is known regarding the impact of these factors on an individual’s susceptibility to environmentally-mediated metabolic disruption. Advances in these areas will be critical for translating EDC science into the clinic to enable physicians to stratify an individual’s risk of developing EDC-induced metabolic disease and to provide direction for treating exposed patients.